Characterization of Temperate LPS-Binding Bordetella avium Phages That Lack Superinfection Immunity - Dorothee Serian; Yury Churin; Jens André Hammerl; Manfred Rohde; Arne Jung; Anja Müller; Min Yue; Corinna Kehrenberg (Microbiology Spectrum, 2023)
ABSTRACT Bordetella avium causes a highly infectious upper respiratory tract disease in turkeys and other poultry with high economic losses. Considering the antimicrobial resistance crisis, bacteriophages (phages) may be an alternative approach for treating bacterial infections such as bordetellosis. Here, we describe seven B. avium phages, isolated from drinking water and feces from chicken and turkey farms. They showed strong bacteriolytic activity with a broad host range and used lipopolysaccharides (LPS) as a host receptor for their adsorption. All phages are myoviruses based on their structure observed by transmission electron microscopy. Genome sequence analyses revealed genome assembly sizes ranging from 39,087 to 43,144 bp. Their permutated genomes were organized colinearly, with a conserved module order, and were packed according to a predicted headful packing strategy. Notably, they contained genes encoding putative markers of lysogeny, indicative of temperate phages, despite their lytic phenotype. Further investigation revealed that the phages could indeed undergo a lysogenic life cycle with varying frequency. However, the lysogenic bacteria were still susceptible to superinfection with the same phages. This lack of stable superinfection immunity after lysogenization appears to be a characteristic feature of B. avium phages, which is favorable in terms of a potential therapeutic use of phages for the treatment of avian bordetellosis. IMPORTANCE To maintain the effectiveness of antibiotics over the long term, alternatives to treat infectious diseases are urgently needed. Therefore, phages have recently come back into focus as they can specifically infect and lyse bacteria and are naturally occurring. However, there is little information on phages that can infect pathogenic bacteria from animals, such as the causative agent of bordetellosis of poultry, B. avium. Therefore, in this study, B. avium phages were isolated and comprehensively characterized, including whole-genome analysis. Although phenotypically the phages were thought to undergo a lytic cycle, we demonstrated that they undergo a lysogenic phase, but that infection does not confer stable host superinfection immunity. These findings provide important information that could be relevant for potential biocontrol of avian bordetellosis by using phage therapy.